2018
DOI: 10.1166/jnn.2018.14259
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Calcium Phosphate Ceramic/(Poly(vinyl alcohol)–Polycaprolactone) Bilayer Nanocomposites-A Bone Tissue Regeneration Scaffold

Abstract: β Tricalcium phosphate ceramic was used to reinforce nanofibers in composite mats produced via electrospinning of poly(vinyl alcohol) (PVA), polycaprolactone (PCL) and (PVA: PCL) bilayers. The role of TCP ceramic on morphology of nanocomposites, crystalline structure, functional groups and thermal behaviour of nanocomposites were characterized by SEM, EDAX, XRD, FTIR and DSC analysis. Ultrathin cross-sections of the obtained nanocomposites were morphologically investigated with SEM and all fabricated composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…PVA has two diffraction peaks at 2θ ~19.2° and 20.2° [ 26 , 27 ], whereas PVP has two broad humps at approximately 2 θ ~11.2° and 21.2° [ 28 ]. As the PVA blended with the PVP, the positions of the diffraction peaks are changed due to the formation of intermolecular hydrogen bonding between the PVA and PVP polymers [ 29 ]. The diffraction patterns of the doped blends have a similar trend as they are loaded with up to 11% TPAI or 6% THAI without any characteristic peaks from the TPAI or THAI salt, indicating a complete dissociation of the salt in the blend matrix.…”
Section: Resultsmentioning
confidence: 99%
“…PVA has two diffraction peaks at 2θ ~19.2° and 20.2° [ 26 , 27 ], whereas PVP has two broad humps at approximately 2 θ ~11.2° and 21.2° [ 28 ]. As the PVA blended with the PVP, the positions of the diffraction peaks are changed due to the formation of intermolecular hydrogen bonding between the PVA and PVP polymers [ 29 ]. The diffraction patterns of the doped blends have a similar trend as they are loaded with up to 11% TPAI or 6% THAI without any characteristic peaks from the TPAI or THAI salt, indicating a complete dissociation of the salt in the blend matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of tricalcium phosphate (TCP) on nanocomposites’ shape, crystalline structure, functional groups, and thermal behavior were studied. SEM was used to examine ultrathin cross-sections of the nanocomposites, which revealed that all except the polycaprolactone (PCL)-TCP fibers had an average fiber diameter (AFD) of about 100 nm [ 52 ]. For bone tissue engineering, metallic implants such as magnesium-based alloy foams may be utilized as a potential scaffold material due to their mechanical strength.…”
Section: Nanocomposite Ceramic’s Potential Role In Bone Regenerationmentioning
confidence: 99%
“…The bioactivity of the scaffolds is increased with combination of the polymers with ceramics such as hydroxyapatite (HA) 7 . Ceramics are other important factors in the preparation of bone scaffolds 24 . In the present study, HA that is one of the main inorganic components of natural bone was selected as the ceramic phase of PCL/PHBV blending.…”
Section: Introductionmentioning
confidence: 99%